2019
DOI: 10.1159/000497226
|View full text |Cite
|
Sign up to set email alerts
|

Raspberries Improve Postprandial Glucose and Acute and Chronic Inflammation in Adults with Type 2 Diabetes

Abstract: Background: Postprandial metabolic impairments in diabetes have been shown to play an important role in vascular complications. Dietary polyphenols and other bioactive compounds in berries have been shown to improve postprandial hyperglycemia and related metabolic impairments, but few clinical studies have been reported in diabetes. Objective: To examine the effects of daily dietary raspberries on postprandial and 4-week fasting glucose, lipids and biomarkers of inflammation in obese adults with type 2 diabete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(96 citation statements)
references
References 40 publications
4
89
2
1
Order By: Relevance
“…Among other commonly-consumed berries, we reported the effects of frozen raspberries in decreasing postprandial glucose and inflammatory biomarkers in T2D adults. 83 Raspberries have been previously shown to decrease postprandial insulin and glucose in adults with insulin resistance and MetS, 77 and in this work, we concluded that raspberries may have a distinct role in ameliorating postprandial dysglycemia in T2D as well.…”
Section: Effects Of Berries On Glycemia and Insulin Resistance In Adusupporting
confidence: 57%
“…Among other commonly-consumed berries, we reported the effects of frozen raspberries in decreasing postprandial glucose and inflammatory biomarkers in T2D adults. 83 Raspberries have been previously shown to decrease postprandial insulin and glucose in adults with insulin resistance and MetS, 77 and in this work, we concluded that raspberries may have a distinct role in ameliorating postprandial dysglycemia in T2D as well.…”
Section: Effects Of Berries On Glycemia and Insulin Resistance In Adusupporting
confidence: 57%
“…Processed red raspberries have been studied for their health benefits in models of age-related chronic diseases. The consumption of frozen red raspberries compared to a control lowered postprandial hyperglycemia and inflammation in adults with prediabetes or diabetes [35,36]. Red raspberry juice intake improved the lipids profile, antioxidant status and reduced the risk of developing atherosclerosis in hamsters consuming an atherogenic diet [37].…”
Section: Discussionmentioning
confidence: 99%
“…In randomized controlled clinical trials, acute interventions with dietary polyphenols have shown promise in mitigating postprandial inflammation. For example, cranberries and raspberries dampened postprandial elevations of serum IL-6 and IL-18, respectively, in adults with obesity and T2D after a HF breakfast [ 56 , 57 ]. Further, Oh et al recently showed that a spice blend supplement (6 g) taken with a HF, high-carbohydrate meal reduced IL-1β, IL-8, and tumor necrosis factor-α secretion by liposaccharide-stimulated (LPS) peripheral blood mononuclear cells of men who had overweight or obesity [ 58 ].…”
Section: Discussionmentioning
confidence: 99%